GROWTH RESPONSE OF SOYBEAN (Glycine max (L.) MERRILL) TO ADDITION SENTANG LEAVES (Azadirachta excelsa (JACK.) JACOBS) AND MINDI LEAVES (Melia azedarach Linn.) - Wijayanto, Nurheni; Dewi, Nilasari; Wardani, Aditya (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Soybeans is one of important food sources in Indonesia mainly as protein resources. The needs of soybeans which increasing and lower number of cultivation land causes soybeans import. Soybeans productivity improvement could be done by agroforestry system. Mindi and sentang are a fast growing species which famously cultivated at this time. One of benefit gained from agroforestry system is providing sources of organic material. Planting combination between mindi and sentang with soybeans could give organic material such as from mindi leaves and sentang leaves. This research aimed to examine the response of soybeans growth to the additional of leaves. The experimental design used was Complete Random Design (CRD) with single factor and seven treatments (control, dry whole, dry chopped, dry powder, wet whole, wet chopped, and wet powder. This research shows that the addition of sentang leaves does not impact to the diameter and height growth. The additional of mindi leaves give not significantly different to the growth of soybeans diameter, total dry mass, and total wet mass. The additional of sentang leaves give effect to the growth of number of leave, total wet mass, total dry mass and total pud mass. The additional of mindi leaves give significant impact to the height, number of leaves, and pot mass. The treatment give best impact to total pud mas was sentang dry leave chopped and mindi dry leave whole.Key words: Agroforestry, Azadirachta excelsa, Glycine max, Melia azedarach